Text Structure Strategies for Improving Expository Reading Comprehension. (22nd May 2017) - Roehling, Julia V.; Hebert, Michael; Nelson, J. Ron; Bohaty, Janet J.
Abstract: Comprehending expository reading material is a challenge for many students. Research has shown that students' expository reading comprehension can improve with the help of text structure instruction. The purpose of this article is to present teachers with a framework for effectively implementing text structure instruction in their classrooms. Within this framework, the authors suggest four possible learning objectives for text structure instruction. They then describe instructional strategies related to each objective and ways to assess whether the objectives were met. Finally, the authors discuss some issues to consider when choosing expository reading material for students and present text structure unit plans for grades 2 and 5 as examples of how teachers might construct a unit.